2022
DOI: 10.3389/fvets.2022.852321
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Produces Amino Acids to Stimulate Protein Synthesis in Ruminal Tissue Explants via the Phosphatidylinositol-4,5-Bisphosphate 3-Kinase Catalytic Subunit Beta–Serine/Threonine Kinase–Mammalian Target of Rapamycin Complex 1 Pathway

Abstract: BackgroundBacillus subtilis is a probiotic strain that is widely used as a feed supplement for ruminants. In this study, one B. subtilis strain isolated from the ruminal fluid of Holstein dairy cows was used for an ex vivo study with ruminal tissue explants. The main goal was to assess the potential endosymbiotic links between B. subtilis and the ruminal epithelium using molecular analyses and amino acid profiling. The explant culture protocol was first optimized to determine the ideal conditions in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Intriguingly, we discovered that RL downregulated TYRP-2 (instead of TYRP-1) mRNA level in HEM cells, which might be linked with tryptophan. Heat-inactivated probiotics have the cell surface proteins that could hydrolyze into amino acids, like tryptophan, phenylalanine and leucine (87). It was reported that tryptophan could be catabolized into propanoate in primary human hepatocytes (88).…”
Section: Rl Exerted the Antiwrinkle Impact In Msf Cellsmentioning
confidence: 99%
“…Intriguingly, we discovered that RL downregulated TYRP-2 (instead of TYRP-1) mRNA level in HEM cells, which might be linked with tryptophan. Heat-inactivated probiotics have the cell surface proteins that could hydrolyze into amino acids, like tryptophan, phenylalanine and leucine (87). It was reported that tryptophan could be catabolized into propanoate in primary human hepatocytes (88).…”
Section: Rl Exerted the Antiwrinkle Impact In Msf Cellsmentioning
confidence: 99%
“…This species, listed in the Qualified Presumption of Safety (QPS) recommended microorganisms intentionally added to food or feed (EFSA BIOHAZ Panel, 2022, 2023a, 2023b), was shown to colonize the gastrointestinal tract of mammals and poultry, in the form of vegetative cells (spores) or forming biofilms, thereby acting as probiotic (Bernardeau et al, 2017; Lee et al, 2019; Mun at al., 2021). In particular, B. subtilis spores added to dairy cattle feed consistently exerted a positive influence on ruminal fermentation, growth, lactation performance, and milk composition (Sun et al, 2011; Sun et al, 2013; Sun et al, 2016; Souza et al, 2017; Choonkham et al, 2020; Wang et al, 2022; Jia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This species, listed in the Qualified Presumption of Safety (QPS) recommended microorganisms intentionally added to food or feed [12], was shown to colonize the gastrointestinal tract of mammals and poultry, in the form of vegetative cells (spores) or by forming biofilms, thereby acting as probiotic [13][14][15]. In particular, B. subtilis spores added to dairy cattle feed consistently exerted a positive influence on ruminal fermentation, growth, lactation performance, and milk composition [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%